Coupling effect of ionic liquids on the mechanical, thermal, and chemical properties of polymer composites: a succinct review - Shamsuri, Ahmad Adlie; Md. Jamil, Siti Nurul Ain; Abdan, Khalina (John Wiley and Sons, 2024)
The growing study of polymer composites has motivated scientists to explore more methodologies to enhance the final demanding properties of polymer composites. Polymer composites have commonly been fabricated using thermosets or thermoplastics with synthetic or natural fillers. Lately, ionic liquids have been applied as coupling agents for polymer composites. In this succinct review, two types of ionic liquids, specifically imidazolium- and phosphonium-based ionic liquids that are applied as coupling agents, are identified. Additionally, the synthesis of ionic liquids with different precursors and reactions is explained. The coupling effect of ionic liquids on the mechanical, thermal, and chemical properties of polymer composites is also succinctly reviewed. The knowledge shown in this review gives a more transparent comprehension of the fabrication of polymer composites coupled with ionic liquids and the essential properties of polymer composites. In conclusion, most imidazolium- and phosphonium-based ionic liquids can improve several mechanical, thermal, and chemical properties of thermoset and thermoplastic composites.